2019
DOI: 10.1115/1.4044015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Fracture Toughness of Tessellated Materials With the Discrete-Element Method

Abstract: Architectured materials contain highly controlled structures and morphological features at length scales intermediate between the microscale and the size of the component. In dense architectured materials, stiff building blocks of well-defined size and shape are periodically arranged and bonded by weak but deformable interfaces. The interplay between the architecture of the materials and the interfaces between the blocks can be tailored to control the propagation of cracks while maintaining high stiffness. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…An alternative method that has been used in analytical models [10,14,22] and in discrete element method (DEM) [15,24,25,38] of 2D brick-and-mortar structures is to use a cohesive zone model (CZM) to describe the deformation and failure response of the soft layers. The CZM is defined by a traction-separation law which inherently incorporates damage.…”
Section: Doi: 101002/adem202301146mentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative method that has been used in analytical models [10,14,22] and in discrete element method (DEM) [15,24,25,38] of 2D brick-and-mortar structures is to use a cohesive zone model (CZM) to describe the deformation and failure response of the soft layers. The CZM is defined by a traction-separation law which inherently incorporates damage.…”
Section: Doi: 101002/adem202301146mentioning
confidence: 99%
“…[2] Another advantage of the structure is its large range of design parameters, which results in a highly tunable response.Many studies have explored the effect of different design parameters on the response of the structure under uniaxial tension, including the aspect ratio of the bricks, [3][4][5][6][7][8][9][10] the relative stiffness between the material of the bricks and the material of the layers, [5,7,[11][12][13] the relative material properties of the layers perpendicular and parallel to the loading direction, [7,10] the volume fraction of each phase, [4,5,7,9] the overlap ratio of the bricks, [4,6,9] and the shape of the tiles. [5,8,[14][15][16][17][18][19][20][21] These parameters have been shown to significantly affect the elastic modulus, yield stress, toughness, and failure regime of the structure. The efficient exploration of these design parameters has been enhanced by the development of models, including analytical models [7,8,10,14,22,23] and computational models, such as lattice spring models, [2,11,12,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigation into these structures has shown that they not only have exceptional combinations of strength and toughness, but that they also exhibit a highly tunable mechanical response. This is due to the large number of design parameters associated with the structure, including their geometric [11,12,15,[22][23][24][25][26][27][28][29][30] and material [18,23,28,31] parameters, and the control of design over multiple length scales [11,17,20,32]. Their tunable response extends the existing design parameter space, broadening the possible applications for this type of structure.…”
Section: Introductionmentioning
confidence: 99%